Cross-Cultural Experiences in Teacher Education: Indonesian Pre-Service English Teachers' Perspectives on International Teaching Practicum - Hasymi, Mutia; Nurkamto, Joko (Universitas Hamzanwadi, 2023)
This study addresses a significant gap in current literature concerning the international teaching practicum experiences of Asian pre-service teachers specializing in English education. Focusing on three Indonesian pre-service teachers, the research explores their experiences during international practicum in the Czech Republic, Thailand, and Malaysia. Methodologically, the study employed in-depth semi-structured interviews, along with the analysis of narrative journals and artifacts from the International Teaching Practicum (ITP) program, following the thematic analysis approach by Braun and Clarke (2006). This involved meticulous examination of data, coding, and thematic classification to derive meaningful interpretations. Key findings highlight the challenges faced by participants, including language barriers and cultural adaptation. Despite these challenges, participants reported substantial growth in confidence and self-assurance, fostered by active participation in teaching and learning activities. Significantly, the practicum provided valuable insights into multicultural education, deepening the participants' understanding of different teaching methodologies, the role of teachers, and the nuances of local educational systems. The implications of this study are far-reaching, particularly in enhancing multicultural competence in teacher education. By shedding light on the under-researched area of international teaching practicum involving Asian contexts, the study contributes essential insights into the evolving landscape of global teacher education.